Manufacturing of high brightness dissolving pulp from sansevieria-trifasciata fiber by effective sequences processes - Yusnimar; Evelyn; Aman, Azka; Chairul; Rahmadahana, Suci; Amri, Amun (Communications in Science and Technology, 2022)
The need of dissolving pulp (DP) for rayon fiber production is increasing rapidly in recent years. Sustainable sources of DP raw materials and an effective manufacturing process are urgently required. This study aims to manufacture dissolving pulp (DP) with high brightness from Sansevieria-trifasciata (ST) fiber through the pre-hydrolysis, soda-Anthraquinone (Soda-AQ) cooking, and chlorine-free bleaching processes. The cellulose content, kappa number, pulp yield, and viscosity were analyzed. The results showed that the ?-cellulose content in ST raw material (39.43%) was relatively similar to the ?-cellulose content in Acacia pulping kraft (39.2%). Furthermore, the variations in pre-hydrolysis time affected the Kappa number, pulp yield, and viscosity. The DP obtained by the elementary chlorine-free (ECF) bleaching process had a viscosity of 9.3 cP, ?-cellulose content of 97.7%, and the brightness of 90.1% which was higher than the ISO standard of pulp brightness. The high DP brightness obtained from this unique combination of pre-hydrolysis, soda-AQ cooking and chlorine-free bleaching sequences has great potential for further development, as it can be used in viscose rayon staple fibers production.